Effects of adding post-workout microcurrent in males cross country athletes - Naclerio, F.; Moreno-Perez, D.; Seijo, M.; Karsten, B.; Larrosa, M.; García-Merino, J. A.; Thirkell, J.; Larumbe-Zabala, E. (European Journal of Sport Science, 2021)
Post-exercise microcurrent based treatments have shown to optimise exercise-induced adaptations in athletes. We compared the effects of endurance training in combination with either, a microcurrent or a sham treatment, on endurance performance. Additionally, changes in body composition, post-exercise lactate kinetics and perceived delayed onset of muscle soreness (DOMS) were determined. Eighteen males (32.8±6.3 years) completed an 8-week endurance training programme involving 5 to 6 workouts per week wearing a microcurrent (MIC, n=9) or a sham (SH, n=9) device for 3-h post-workout or in the morning during non-training days. Measurements were conducted at pre- and post-intervention. Compared to baseline, both groups increased (P<0.01) maximal aerobic speed (MIC, pre =17.6±1.3 to post=18.3±1.0; SH, pre=17.8±1.5 to post =18.3±1.3 km.h-1) with no changes in O2peak. No interaction effect per group and time was observed (P=0.193). Although both groups increased (P<0.05) trunk lean mass (MIC, pre=23.2±2.7 to post=24.2±2.0; SH, pre=23.4±1.7 to post=24.3±1.6 kg) only MIC decreased (pre=4.8±1.5 to post=4.5±1.5, p=0.029) lower body fat. At post-intervention, no main differences between groups were observed for lactate kinetics over the 5 min recovery period. Only MIC decreased (P<0.05) DOMS at 24-h and 48-h, showing a significant average lower DOMS score over 72-h after the completion of the exercise-induced muscle soreness protocol. In conclusion, a 3-h daily application of microcurrent over an 8-week endurance training programme produced no further benefits on performance in endurance-trained males. Nonetheless, the post-workout microcurrent application promoted more desirable changes in body composition and attenuated the perception of DOMS over 72-h post-exercise.